A/Political Education: A Survey of Quebec Students’ Perceptions of Their Citizenship Education - Fournier-Sylvester, Nicole (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
This survey of 370 recent high school graduates reveals that history and citizenship courses in Quebec focus on cultural and religious viewpoints, favour a transmission approach to learning, and fail to connect the political process to students’ concerns and interests. Without a clear conception of citizenship as a reference point, this curriculum appears to neglect the development of agency around civic engagement and social change. Recommendations on how to improve the program are guided by students’ answers to open-ended questions and current scholarship on the need for a more critical analysis of national and global diversity and inequality in school curriculums.